Pengaruh Senam Aerobic Low Impact Terhadap Penurunan Tingkat Dismenore Pada Remaja Putri Di MA Tahfidz Rokan Hulu Tahun 2024 - Nana Aldriana; Rika Herawati; Ermiza; Rizka Ningsih (Journal of Innovative and Creativity, 2025)
Dysmenorrhea is a symptom that can occur in women and experience pain during menstruation. Dysmenorrhea can be overcome with low impact aerobic exercise . Low impact aerobics is an aerobic exercise movement that is done lightly (light impact), the movement does not require strength and violence and is relatively slower following the rhythm of the music . The purpose of this study was to determine the Effect of Low Impact Aerobic Exercise on Reducing Dysmenorrhea Levels in Adolescent Girls at MA Tahfidz Rokan Hulu in 2024. This type of research is quantitative research with a Pre-Experimental Research Design with a One Group Pretest-Posttest design . The population in this study was 110 people and the sample was 30 people. Sampling used the Purposive Sampling technique . Data analysis used the Dependent T test. The results of the analysis showed that there was a decrease in the level of dysmenorrhea by 30 respondents. The average pain scale of respondents before doing low impact aerobic exercise was 4.80 and after doing low impact aerobic exercise was 1.10 with an average before and after doing yoga was 3,700 with the results of the Dependent T test obtained p value = 0.000 <0.05, this means p value <0.05. So it can be concluded that there is an effect of giving low impact aerobic exercise on reducing the level of dysmenorrhea in female adolescents at MA Tahfidz Rokan Hulu . It is expected that after the study is conducted, respondents can use low impact aerobic exercise to treat dysmenorrhea and avoid the use of pharmacological techniques to treat dysmenorrhea. Keywords: Adolescents, Dysmenorrhea, Low impact aerobic exercise , Pain scale